Intrapartum Cervical Assessment Clinical Skills Lab (Out of Print) - Rachel Hansen; Francis Nuthalapaty (Association of American Medical Colleges, 2010)
Abstract This online resource contains an accurate assessment of cervical dilation and effacement, and is essential to effective labor management. Current approaches to training medical students in this skill often rely upon limited bedside examination of real patients, or less often, on expensive simulation models which do not effectively demonstrate progressive dilation and effacement. The Intrapartum Cervical Assessment Clinical Skills Lab was designed to address this problem, incorporating simple, inexpensive clay models to improve student visual and tactile appreciation of cervical dilation and effacement and improve accuracy in assessment. All lab materials are available on a website with multiple resources that have been developed to aid the instructor in easily integrating the material into his or her curriculum. The resource include a 12-minute didactic lecture for students to view online, which covers pertinent pelvic anatomy, stages of labor, steps in cervical assessment, as well as techniques, risks, benefits, and indications for cervical assessment. A Readiness Assessment Quiz, along with detailed explanations of answers, complements the lecture and assesses student's retention and preparedness for the laboratory session. A 10-minute instructor's guide with a review of the current literature on this topic, step-by-step instructions for forming the clay models, and suggestions for implementing the lab is also available. The same instructor's material is covered in written form in the lab manual which accompanies this paper. Finally, the toolkit provides a model worksheet for teaching dilation and effacement, a skills assessment worksheet for testing purposes, and a checklist for use in an OSCE evaluation. This lab has been taught to University of South Carolina School of Medicine's third-year medical students as part of the introductory curriculum for the OBGYN medical student clerkship at Greenville Memorial Hospital since July 2007. Both students and residents have given positive feedback regarding improvements in skill and accuracy on the wards.